Senses of body image in adolescents in elementary school - Silva, Maria Lídia de Abreu; Taquette, Stella Regina; Coutinho, Evandro Silva Freire (Revista de Saúde Pública, 2014)
OBJECTIVE : To comprehend the perception of body image in adolescence. METHODS : A qualitative study was conducted with eight focus groups with 96 students of both sexes attending four public elementary school institutions in the city of Rio de Janeiro, Southeastern Brazil, in 2013. An interview guide with questions about the adolescents’ feelings in relation to: their bodies, standards of idealized beauty, practice of physical exercise and sociocultural influences on self-image. In the data analysis we sought to understand and interpret the meanings and contradictions of narratives, understanding the subjects’ context and reasons and the internal logic of the group. RESULTS : Three thematic categories were identified. The influence of media on body image showed the difficulty of achieving the perfect body and is viewed with suspicion in face of standards of beauty broadcast; the importance of a healthy body was observed as standards of beauty and good looks were closely linked to good physical condition and result from having a healthy body; the relationship between the standard of beauty and prejudice, as people who are not considered attractive, having small physical imperfections, are discriminated against and can be rejected or even excluded from society. CONCLUSIONS : The standard of perfect body propagated by media influences adolescents’ self-image and, consequently, self-esteem and is considered an unattainable goal, corresponding to a standard of beauty described as artificial and unreal. However, it causes great suffering and discrimination against those who do not feel they are attractive, which can lead to health problems resulting from low self-esteem.